Process Design for Hydroforming of Lightweight Metal Sheets at Elevated Temperatures - Novotny, Stefan; Geiger, Manfred (Journal of Materials Processing Technology, 2003)
Lightweight materials like aluminium and magnesium alloys offer a high potential for weight reduction in automotive and other transportation vehicle construction. The high alloy percentages in aluminium alloys and the hexagonal structure of magnesium, however, lead to a relatively low formability of the sheet materials which can be enhanced by conducting the forming processes at elevated temperatures up to the recrystallisation temperature. This strategy is commonly used in rolling and forging, but still rises problems in sheet forming. In a research project at the chair of manufacturing technology the process of hydroforming of aluminium and magnesium sheet material shall be enhanced to be conducted at elevated temperatures. Based on material tests to determine the behaviour of different aluminium and magnesium alloys at elevated temperatures, appropriate hydroforming strategies for these materials have to be developed. Laboratory systems for the uniaxial tension test, the free hydraulic bulging of sheet material and for strip drawing, all at elevated temperatures, were built up and used as models for the design of a production system for hydroforming with a warm pressure fluid. The tests were also simulated with an FEM-system to show the restrictions and the potentials of simulation tools for this production strategy, aiming at the subsequent simulation of the complete hydroforming process. © 2003 Elsevier Science B.V. All rights reserved.
LFT Import::2019-07-15 (926)
Keywords: Aluminium; Elevated temperature; FEM simulation; Hydroforming; Lightweight construction; Magnesium